The promise : President Obama, year one - Alter, Jonathan (New York, NY : Simon & Schuster, 2010)
Jonathan Alter, one of the country's most respected journalists and historians, uses his unique access to the White House to produce the first inside look at Obama's difficult debut. In Alter's telling, the real Obama is an authentic, demanding, unsentimental, and sometimes overconfident leader.
Jonathan Alter, one of the country's most respected journalists and historians, uses his unique access to the White House to produce the first inside look at Obama's difficult debut. In Alter's telling, the real Obama is an authentic, demanding, unsentimental, and sometimes overconfident leader.
Obama takes charge -- White House-in-waiting -- Grant Park -- The cabinet maker -- Picking Hillary -- Instant president -- Historic inauguration -- Sea legs -- Zen temperament -- Rahmbo -- The shovel brigade -- Larry and Tim -- The un-Bubba -- Global reset -- Tyrannosaurus Rx -- Professor-in-chief -- Off-hours -- The skinny guy and the fat cats -- Modus Obama --'Don't blow it!' -- Chaos-istan -- The perfect and the good -- Epilogue.
Includes bibliographical references and index.
Keywords: Obama, Barack; Obama, Barack -- Friends and associates; Presidents -- United States -- Biography; United States -- Politics and government -- 2009-